Exploring the electronic structure and optical properties of double perovskite Ba2RESbO6 (RE = Ho, Er) from first-principles calculations. (3rd October 2017) - Halder, Saswata; Mukherjee, Rajesh; Dutta, Alo; Sinha, T. P.
ABSTRACT: First principles density functional theory (DFT) calculations are performed to explore the electronic structure and optical properties of Ba2 RESbO6 (RE = Ho, Er) in the cubic symmetry using the experimental lattice parameters. The calculations are performed in two different DFT approaches, FP-LAPW method and plane wave pseudo potential method. The electronic band structures of these compounds were analyzed using the generalized gradient approximation (GGA). A direct band gap (Γ-Γ for Ba2 HoSbO6 and Ba2 ErSbO6 was obtained. The calculated optical properties were analyzed from band structure calculations. The Born effective charges and the static dielectric tensor of these materials were also calculated.